Examining The Key Succes Factors of Islamic Cooperatives in A Resilient Global Economy - Tripalupi, Ramadhani Irma; Anggahegari, Prameshwara Anggahegari; Putri, Tasya Aulia; Putri, Aliqa Riyana; Sabita, Amira (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2025)
Within the framework of globalization, cooperatives may serve as an effective remedy for issues related to unemployment, poverty, and economic disparity. Consequently, assistance from the economic ecosystems is essential to fortify Islamic cooperatives. This study seeks to uncover and thoroughly analyses the critical aspects that contribute to the development of Islamic cooperatives in Indonesia within a globally resilient economy. This study employs descriptive methodologies and qualitative approaches. The data sources are both primary and secondary, employing triangulation techniques to assess trustworthiness through the triangulation of data sources and data collection methods. The study's findings reveal that the efficacy of Islamic cooperatives in Indonesia within a globally resilient economy can be attributed to six principal factors: leadership grounded in Islamic values, effective governance, active member participation, high-quality human resources, external environmental support, and strategies for global economic resilience. There are several strategies of Islamic cooperatives in the resilient global economy, but the application of Islamic principles is the main foundation. This proves the role of Islamic cooperatives in the ongoing economic activities are ethical and sustainable.